Study on the correlation between TCM syndrome differentiation and immune inflammation index of Sjogren's syndromehttp://www.hnykdxxb.com/PDF/202114/01.pdf - Gui-Zhen Wang (Journal of Hainan Medical University, 2021)
Objective: To observe the relationship between the distribution of TCM Syndromes of primary Sjogren's syndrome (pSS) and the changes of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), tumor necrosis factor -α (TNF-α), interleukin-6 (IL-6), immunoglobulin IgA, IgG and IgM. Methods: 157 diagnosed PSS patients were divided into dampness heat obstructing collaterals syndrome, dryness evil invading lung syndrome, Qi blood stasis syndrome, liver kidney yin deficiency syndrome and Qi Yin deficiency syndrome according to TCM syndrome differentiation standard. The age, course of disease, general health score in international universal quality of life scale, self rating Anxiety scale (SAS), self rating Depression Scale (SDS) and erythrocyte sedimentation rate were observed and detected (ESR, C-reactive protein (CRP), tumor necrosis factor-α(TNF-α), interleukin-6 (IL-6), immunoglobulin IgA, IgG and IgM and other immune inflammatory indexes were detected. The relationship between different TCM Syndromes of PSS and molecular level changes of immune inflammatory indexes was analyzed and compared, as well as the impact on quality of life and mental emotion. Results: The overall health score of patients with Qi Yin deficiency syndrome was significantly lower than that of patients with dampness heat obstructing collaterals and dampness evil invading lung syndrome (P < 0.01), while the SAS and SDS scores of patients with Qi Yin deficiency syndrome were significantly higher than those of patients with dampness heat invading lung syndrome and dampness heat obstructing collaterals syndrome (P < 0.05, P< 0.01); ESR, CRP, RF, TNF-α, IL-6, IgA, IgG and IgM related laboratory indexes of patients with dampness heat obstructing collaterals syndrome were significantly higher than those of patients with dry evil invading lung syndrome, liver kidney yin deficiency syndrome and liver kidney yin deficiency syndrome Qi Yin deficiency syndrome and Qi blood stasis syndrome (P<0.05, P<0.01). Correlation test found that the above five syndrome types were positively correlated with hs-CRP, IL-6, TNF-ɑ indicators (P<0.05). Conclusion: The overall health, SAS, SDS and related hs-CRP, IL-6, TNF-ɑ and some others indexes of SS patients are associated with TCM syndromes.